Pemanfaatan Tepung Biji Nangka dan Tepung Ampas Kelapa sebagai Bahan Pensubstitusi Terigu dalam Pembuatan Roti Manis - Rika Andeska; Yusmarini Yusmarini; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aimed to know the best of substitute ratio of jackfruit seed powder and coconut dregspowder of wheat flour for the best quality of sweet bread. Research method used completely randomized designed which consisted of six treatments and each treatment wasrepeated three times. Treatments of jackfruit seed powder and coconut dregs powder of wheat flour were TBA0 (100% wheat flour), TBA1 (70% of wheat flour, 30% of jackfruit seed powder and 0% coconut dregs powder), TBA2 (70% of flour, 27,5% jackfruit seed powder and 2,5% coconut dregs powder), TBA3 (70% of wheat flour, 25% jackfruit seed powder and 5% coconut dregs powder),  TBA4 (70% of wheat flour, 22,5% jackfruit seed powder and 7,5% coconut dregs powder) and TBA5 (70% of wheat flour, 20% jackfruit seed powder and 10% coconut dregs powder). Data were statistically analyzed by analysis of variance (ANOVA) and proceeded with duncan’s new multiple range test (DNMRT) at 5% level. The results showed that the sweet bread chosen treatment is TBA2with moisture content of 29.28%, ash content of 2.52%, fat content of 10.29%, protein content of 7.48%, crude fiber 1.68% and has slightly flavor, distinctive aroma of coconut, the more soft crust texture, the more soft crumb texture, brownish-yellow crust color, yellowish-white crumbs color and favored overall by panelists.Keywords: Jackfruit seed powder, coconut dregs powder, sweet bread.